ASTROMETRY OF Χ AND H PERSEI BASED ON PROCESSING OF DIGITIZED PLATES OF ARCHIVE OF THE ASTRONOMICAL INSTITUTE OF THE ACADEMY OF SCIENCES OF THE REPUBLIC OF UZBEKISTAN - Muminov, M. M.; Yuldoshev, Q. X.; Ehgamberdiev, Sh. A.; Kahharov, B. B.; Andruk, V. N.; Protsyuk, Yu. I. (Одеські астрономічні публікації, 2014)
Work is done with Epson Expression 10000XL scanner of Astronomical Institute (AI) of the Academy of Sciences of Uzbekistan. The plates were exposed with the Normal astrograph (D/F = 330mm / 3467mm, M = 59.56"/mm). The digitization of plates with (16x16) cm in size was made with resolution of 1200 dpi (1px = 1.25"). Test research was done using plates at first (1935.0) and second (1976.9) epochs in the sky area around the χ and h Persei clusters (field of view is 2°x2°). Coordinates and B-magnitude of stars were obtained using TYCHO-2 as the reference catalog. Errors of coordinate differences and proper motions for reduced and reference stars are respectively σαδ = ±0.074" and σμαδ = ±0.0018"/year (655 stars). Errors of photometry are σm = ±0.065m and σB = ±0.208m for internal convergence and in comparison with TYCHO-2 catalog. Comparison with UCAC4 catalog for 8123 stars with B≤17.5m gave us errors of σαδ = ±0.28", σμαδ = ±0.0075"/year and σm = ±0.139m for the equatorial coordinates, proper motions and magnitudes, respectively.